The Role of Honour in Egils saga - Barreiro, Santiago Francisco
The aim of this text is to assess the role that honour plays in a long prose text composed in Iceland c.1220-1240, Egils saga Skalla-Grímssonar. First, we present the main theoretical and historiographical views on honour, both as a general concept and applied specifically to the Icelandic Middle-Ages. Furthermore, we analyze the vocabulary of honour present in the saga in order to identify figures in it which could have been considered as models of honourable behaviour. Finally, we discuss the notion of honour as a commodity and instead propose an alternative view. We hold that honour can be compared with the notion of inalienable wealth and exemplify our stance with a short case study of a scene in the saga. L'objectif de cette étude est d'évaluer le rôle joué par l'honneur dans un un texte en prose composé en Islande entre 1220-1240, Egils saga Skalla-Grímssonar. Tout d'abord, nous présenterons les principales positions théoriques et historiographiques sur l'honneur, en tant que concept général mais également appliqué à l'Islande médiévale. Ensuite, nous analyserons le vocabulaire de l'honneur présent dans la saga afin d'identifier les figures qui ont pu être considérées comme des modèles de comportement honorable. Enfin, nousdiscuterons l'idée selon laquelle l'honneur serait une marchandise et proposerons une vision alternative. Nous estimons que l'honneur peut être comparé à la notion de richesse inaliénable et illustrerons notre position par une brève étude de cas sur une scène de la saga. Fil: Barreiro, Santiago Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina